The Physical Education Class Perceived by Schoolchildren from 6 to 8 Years Old Expressed through Drawings - Javier Cachón-Zagalaz; Déborah Sanabrias-Moreno; María Sánchez-Zafra; Amador Jesús Lara-Sánchez; María Luisa Zagalaz-Sánchez (MDPI AG, 2021)
Physical Education is one of the subjects that arouses the most interest in children. The aim of this study is to find out the opinion that primary school students have about the Physical Education class. Drawings from a sample of 62 students from an educational centre in the city of Jaén, aged between six and eight years old, were analysed. The results show that the larger size of the drawings corresponds to the aspects that are to be emphasised. This subject is carried out regularly in the sports pavilion of the centre, making frequent use of materials such as sticks, hoops or balls. Cheerful colours are used, reflecting their enthusiasm for the subject. The smiling facial expression represents the schoolchildren's interest in the subject. The most popular games or sports are basketball and pichi, both of them collective.